Deep learning based crowd monitoring and person identification system - Haque, Mohammad Fahim; Sarkar, Dipto; Choudhury, Tawhid Al Muhaimin; Rafi, Samiul Hoque; Rahim, Md Shajidur (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.